Benefit of extracorporeal membrane oxygenation in major burns after stun grenade explosion: Experience from a single military medical center. Issue 3 (May 2017) - Hsu, Po-Shun; Tsai, Yi-Ting; Lin, Chih-Yuan; Chen, Shyi-Gen; Dai, Niann-Tzyy; Chen, Cheng-Jung; Chen, Jia-Lin; Tsai, Chien-Sung
Highlights: VV-ECMO can be an alternative treatment for ARDS caused by major burn. VA-ECMO provides no benefits for hemodynamic support in major burn patients. Restoring intravascular volume should be the priority before utilization of ECMO. Abstract: Introduction: Explosion injury is very common on the battlefield and is associated with major burn and inhalation injuries and subsequent high mortality and morbidity rates. Here we report six victims who suffered from explosion injuries caused by stun grenade; all were treated with extracorporeal membrane oxygenation (ECMO) as salvage therapy. This study was aimed to evaluate the indications and efficacy of ECMO in acute and critically ill major burn patients. Methods: This was a retrospective analysis of six patients from Tri-Service General Hospital, National Defense Medical Center in Taiwan. All suffered from major burns with 89.0 ± 19.1% average of total body surface area over second degree (TBSA; range, 50–99%). ECMO was used due to inhalation injury in five patients and cardiogenic shock in one patient. The average interval to start ECMO was 26.5 ± 19.0 h (range, 14–63 h). Venoarterial ECMO was used on in four patients due to unstable hemodynamic status, whereas venovenous ECMO was used in two patients for sustained hypoxemia. Results: All patients had rhabdomyolysis with acute renal failure. The average duration of ECMO was 169.6 ± 180.9 h (range, 27–401 h). All patients developed coagulopathy and needed debridement surgery during ECMO support, and five underwent torso escharotomy due to inspiratory compromise. Only one patient whose second and third degree burns covered 50% TBSA was successfully weaned from ECMO and survived; he was discharged after 221 hospital days. All patients who died had second and third degree burns covering over 90% of their TBSA. Three patients died of multiple organ failure, one died of septic shock, and the other died of cardiogenic shock. Overall survival rate was 16.7%. Conclusions: In acute and critically ill major burn patients, ECMO could be considered as a salvage therapy, particularly in those with inhalation injury and burn-related acute respiratory distress syndrome. However, ECMO does not seem to provide benefits for circulatory support in those with hemodynamic compromise. The use of ECMO in these patients is still investigational, as our data provided no benefit in terms of the outcomes or survival, particularly in those with more than 90% TBSA burns.